Low Carbon Concentration Feeding Improves Medium-Chain-Length Polyhydroxyalkanoate Production in Escherichia coli Strains With Defective β-Oxidation - Mohd Fadzil, Fakhrul Ikhma; Mizuno, Shoji; Hiroe, Ayaka; Nomura, Christopher T.; Tsuge, Takeharu (Frontiers in Bioengineering and Biotechnology, 2018)
Medium-chain-length (MCL) polyhydroxyalkanoates (PHAs) of near homopolymeric composition are unnatural polymers, having almost identical repeating units throughout the polymer chain. These homopolymeric PHAs can be produced by β-oxidation defective bacterial hosts. Escherichia coli is an attractive workhorse for the production of such genetically engineered PHAs; however, achieving efficient production of the near homopolymers by β-oxidation defective strains is a major challenge because of a lack of process development studies. In order to address this issue, we investigated the optimization of carbon feeding for efficient production of MCL-PHAs by an E. coli strain with defective β-oxidation, LSBJ. Engineered bacteria were cultured in shake-flasks with intermittent feeding of a fatty acid substrate [either decanoate (C10) or dodecanoate (C12)] at various concentrations together with a co-carbon source (glucose, glycerol, or xylose) in order to support cell growth. It was found that feeding low concentrations of both fatty acids and co-carbon sources led to an enhanced production of MCL-PHAs. Additionally, the supplementation of yeast extract improved cell growth, resulting in achieving higher titers of MCL-PHA. As a result, poly(3-hydroxydecanoate) [P(3HD)] and poly(3-hydroxydodecanoate) [P(3HDD)] were produced up to 5.44 g/L and 3.50 g/L, respectively, as near homopolymers by employing the developed feeding strategy. To the best of our knowledge, we record the highest titer of P(3HD) ever reported so far.